2006
DOI: 10.1128/aem.01179-06
|View full text |Cite
|
Sign up to set email alerts
|

The Mosaic Nature of Intergenic 16S-23S rRNA Spacer Regions Suggests rRNA Operon Copy Number Variation in Clostridium difficile Strains

Abstract: Clostridium difficile is a major spore-forming environmental pathogen that causes serious health problems in patients undergoing antibiotic therapy. Consequently, reliable and sensitive methods for typing individual strains are required for epidemiological and environmental studies. Ribotyping is generally considered the best method, but it fails to account for sequence diversity which might exist in intergenic 16S-23S rRNA spacer regions (ISRs) within and among strains of this organism. Therefore, this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
52
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 72 publications
7
52
0
Order By: Relevance
“…In general, these studies demonstrated a markedly higher heterogeneity of this region compared with the 16S rRNA gene to differentiate closely related taxa. The mosaic pattern of the ITS described for other genera/species has revealed that the presence or absence of one or more regions (also known as block types) were the reason for the length differences (Sadeghifard et al, 2006). Similar patterns were observed in this study for all the F. nucleatum subspecies, where the operon's variability was based mainly on the presence or absence of these block types.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…In general, these studies demonstrated a markedly higher heterogeneity of this region compared with the 16S rRNA gene to differentiate closely related taxa. The mosaic pattern of the ITS described for other genera/species has revealed that the presence or absence of one or more regions (also known as block types) were the reason for the length differences (Sadeghifard et al, 2006). Similar patterns were observed in this study for all the F. nucleatum subspecies, where the operon's variability was based mainly on the presence or absence of these block types.…”
Section: Discussionsupporting
confidence: 71%
“…Using the ITS region, several studies have investigated species/subspecies and phylogenetic relationships from a range of important clinical isolates including the genus Fusobacterium (Christensen et al, 1999;Narayanan et al, 2001;Conrads et al, 2002;Sadeghifard et al, 2006). In general, these studies demonstrated a markedly higher heterogeneity of this region compared with the 16S rRNA gene to differentiate closely related taxa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather, their over-representation in our libraries may be a consequence of extraction/PCR bias or a high number of rRNA operons per cell. Some members of the Clostridium (in the order Clostridiales along with Acetobacterium) have X10 rRNA operons (Rainey et al, 1996;Brü ggemann et al, 2003;Acinas et al, 2004;Sadeghifard et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In many organisms, intragenomic variability consists of only a few substitutions over the entire ITS length, and results from the presence or absence of tRNA genes. However, intragenomic variability (mosaic-like structure) has been also detected in the bacterial ITS [2][3][4][5][6]. To date, mosaic-like structures have been detected in the non-thermophilic bacteria Salmonella enterica, Haemophilus parainfluenzae, Staphylococcus aureus, Vibrio cholerae, Vibrio mimicus, Vibrio parahaemolyticus, Myxobacterium spp., Acinetobacter baylyi, Photobacterium damselae and Clostridium difficile [2,3,5,[7][8][9].…”
Section: Introductionmentioning
confidence: 99%